Market dynamics, dynamic resource management and environmental policy in the context of (strong) sustainability - Torben Klarl (Universität Augsburg, Institut für Volkswirtschaftslehre, 2010)
In this paper, we investigate the relationship between market dynamics, dynamic resource management and environmental policy. In contrast to static market entry games, this paper draws attention to the effects of market dynamics on resource dynamics et vice versa, because (1) we show that feedback processes are necessary for obtaining a better understanding of what drives the dynamics between the evolution of common-pool resources and the number of harvesters and more importantly, (2) this analysis provides an environment discussing sustainability in an appropriate inasmuch dynamic way. The paper makes following major points: (1) Interpreting the monopoly-scenario as a non-cooperative solution and the firm coexistence solution as a cooperative solution, it is shown that the coexistence solution of this model implies a degenerate saddle-node equilibrium. (2) An increasing number of harvesters does not necessarily imply a lower stock of the common-pool resource in the long run. (3) The paper introduces a way establishing an output-sharing solution by implementing an output tax, which turns out to be a pure effort tax in the long run. (4) Strong resource sustainability is not possible, given cost reducing technological progress is relevant and policy interventions ceased. With respect to environmental policy, we can conclude that a tax scheme is not a substitute to a partnership solution dealing with the common-pool problem, but is treated as an instrument establishing such a solution in the sense of a policy mix approach.
urn:nbn:de:bvb:384-opus4-711080
Keywords: Q28; Q57; C61; 330; Sustainability; resource management; environmental policy; common resources; population dynamics; Gemeingüter; Ressourcenökonomik; Umweltpolitik; Industrieökonomik; Nachhaltige Entwicklung; Theorie